Consumption inequality and partial insurance - Richard W. Blundell; Luigi Pistaferri; Ian Preston (Institute for Fiscal Studies (IFS), 2004)
This paper describes the transmission of income inequality into consumption inequality and in so doing investigates the degree of insurance to income shocks. It combines panel data on income from the PSID with consumption data from repeated CEX cross-sections and distinguishes between permanent and transitory income shocks. We find some partial insurance of permanent income shocks with more insurance possibilities for the college educated and those nearing retirement. We find little evidence against full insurance for transitory income shocks except among low income households. Tax and welfare benefits are found to play an important role in insuring permanent shocks. Adding durable expenditures to the consumption measure suggests that durable replacement is an important insurance mechanism, especially for transitory income shocks.
Keywords: D52; D91; I30; 330; Consumption; Insurance; Inequality; Verbraucherausgaben; Haushaltseinkommen; Schock; Schätzung; Versicherung; USA